Analisis Efektivitas Penerimaan Pajak Kendaraan Bermotor Di Kabupaten Flores Timur Tahun 2017 - 2021 - Zepherinus Wilhelmus Ama Misi Pulang; Agus Budi Waluyo (Jurnal Ilmu Administrasi Publik, 2023)
The phenomenon in this study is due to the discovery of a decreasein The Realization of Motorized Vehicle Tax Revenue in the last three years 2019, 2020, and 2021. So that the SAMSAT Office in the East Flores Regency needs to increase The Effectiveness of Motorized Vehicle Tax Revenue, therefore is important to research that information. The purpose of this study was to determine the evectiveness of motorized vehicle Tax Revenue in East Flores Regency as well as the inhibiting factors and efforts made to increase The Effectiveness of Motorized Vehicle Tax Revenue. This research uses descriptive research with a qualitative approach. The research location in this study was SAMSAT, East Flores Regency. The results of this study indicate that it is significantly positive that taxpayers in East Flores Regency have understood the SAMSAT program. There are also inhibiting factors in its implementation, namely The Community’s Economic Factors, The Lack of Public Understanding of The Obligations of Motorized Vehicle Owners, and The Location of Taxpayers who are far from the SAMSAT Ofice. Even though there are inhibiting factors for SAMSAT, East Flores Regency also has efforts to increase Motorized Vehicle Tax Revenue.